2010
DOI: 10.1016/j.jcin.2009.10.033
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship and Threshold of Stent Length With Regard to Risk of Stent Thrombosis After Drug-Eluting Stent Implantation

Abstract: Length of the stented segment was independently associated with the incidence of ST and death or myocardial infarction after DES implantation. The value of stent length >or=31.5 mm is a threshold for the prediction of ST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
72
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(83 citation statements)
references
References 26 publications
6
72
1
4
Order By: Relevance
“…Stent length has been considered as an important predictor of adverse clinical outcomes after PCI [36,37]. Our data also demonstrated that stent length was one of the predictors of TLR in HD patients after the implantation of DES.…”
Section: Discussionsupporting
confidence: 72%
“…Stent length has been considered as an important predictor of adverse clinical outcomes after PCI [36,37]. Our data also demonstrated that stent length was one of the predictors of TLR in HD patients after the implantation of DES.…”
Section: Discussionsupporting
confidence: 72%
“…In addition, although a complete coverage of diffuse disease is one of the strategies for prevention of SER, multiple long stent implantation may lead to a high incidence of periprocedural myocardial infarction and late stent thrombosis. 14,15 In the present study, we proposed new OCT criteria for stent landing zone to minimize SER. Even in cases with diffuse disease, there might be some segments with an OCT-measured lipid arc of <185°, which could be used for a stent landing zone.…”
Section: Discussionmentioning
confidence: 99%
“…1 Furthermore, first-generation DESs are associated with delayed arterial healing and potential inflammation, as well as a propensity for late thrombosis, especially in high-risk lesions such as long coronary segments. 2 Therefore, the development of newer-generation DESs that ensure both safety and efficacy has become a matter of intensive investigation. These newergeneration DESs use innovative stent platforms, polymers, and a variety of drugs.…”
mentioning
confidence: 99%
“…3,4 Recently, several trials revealed that the outcomes of a newly developed biodegradable polymer-coated biolimus A9-eluting stent (BES) and a platinum chromium everolimuseluting stent (PtCr-EES) were favorable. [1][2][3][4][5] To date, no investigations have compared the benefits of the biodegradable polymer-based BES with the durable polymer PtCr-EES for the treatment of long coronary artery disease. Because of their severity, long coronary artery lesions may be a practical target to assess the anticipated high antirestenotic efficacy and safety of these newer devices.…”
mentioning
confidence: 99%